Optimizing Restaurant Taxes in Increasing Regional Original Revenue (Case Study at the Bojonegoro Regency Regional Revenue Office) - Heny Suhindarno; Beny Priyo Utomo (Journal of Research in Social Science and Humanities, 2024)
This research aims to identify and analyze optimization strategy of restaurant tax in increasing local revenue and strengthening the fiscal independence of Bojonegoro Regency. (PAD) and strengthen the fiscal independence of Bojonegoro Regency. The method used method used is a qualitative descriptive approach with data collection techniques data collection techniques through interviews, observation, and documentation of the Regional Revenue Office and restaurant businesses. Regional Revenue and restaurant business actors. The results showed that the integration of payment system digitization, such as e-Mamin application, e.SPPT, and virtual account, is effective in increasing tax revenue and compliance. application, e.SPPT, and virtual account, effectively increases tax revenue and taxpayer compliance, although it is still faced with obstacles. taxpayers although still faced with obstacles of low taxpayer awareness and limited human resources. and limited human resources. The implications of this research emphasize the importance of developing tax information technology, increasing the capacity of human resources, and enforcement of sanctions to support transparency and effectiveness of restaurant tax collection. restaurant tax collection. The main contributions of this research are an in-depth understanding of the role of digitalization and inter-agency synergies in local tax optimization, which provides new contextual insights. optimization of local taxes, which provides new contextual insights on local fiscal management in the era of fiscal autonomy. regional fiscal management in the era of fiscal autonomy. This research is expected to to be a strategic reference for policymakers in strengthening the independence of local independence through service innovation and adaptive tax management.